An Analysis of APB Opinion Coverage in the CPA Examination. - Balke, Thomas E.; Harris, John K. (The Accounting Review, 1976)
Abstract Knowledge of the coverage of Accounting Principles Board Opinions (APBs) in the Certified Public Accountant (CPA) examination is useful to the accounting educator in several ways. First, students often want to know the likelihood that questions and problems related to the most recently issued APBs will be included in the upcoming examination and the emphasis usually placed on APBs in each part of the examination. Second, financial accounting course content and examinations could be improved by being aware of how the Board of Examiners of the American Institute of Certified Public Accountants examines CPA candidates on APBs. The findings of the study of this article are that, the coverage of Opinions has been highly selective in both Auditing and Practice but has been more comprehensive in Theory; thirteen of the APBs covered have appeared within 6 months after their issuance and three of the others appeared less than 6 months after their issuance; the relative weight of Opinions, in terms of time, in the examination parts has been 19.0 percent in Theory, 8.8 percent in Practice and 2.0 percent in Auditing; wide variation of coverage has occurred from one examination to another in all three parts; and there has been extensive coverage in the Theory and Practice parts of the 1972-1974 examinations.